Bridging Knowledge Gaps in Sexual Violence Prevention among Klaten’s Women Organizations - Ismi Dwi Astuti Nurhaeni; Sajida Sajida; Rina Herlina Haryanti; Asal Wahyuni Erlin Mulyadi; Sri Yuliani (FOUNDAE (Foundation of Advanced Education), 2026)
Sexual violence in Indonesia remains a persistent social problem rooted in structural gender inequality, patriarchal norms, and emerging forms of digital violence. This study aims to identify knowledge gaps and evaluate the effectiveness of a capacity-building intervention designed to strengthen women’s organizations in preventing sexual violence and supporting victim-centered responses. The study involved 31 women’s organizations in Klaten Regency, Indonesia. A quasi-experimental pre-test and post-test design was employed to measure participants’ knowledge across four domains: conceptual understanding of sexual violence, recognition of causal factors, victim-friendly prevention and response, and ethical digital campaigning. Data were collected using a structured 20-item questionnaire administered before and after the intervention, and analyzed using descriptive statistical comparison of response proportions. The results indicate notable improvements in several areas. Recognition of structural power imbalance as a cause of sexual violence increased from 77% to 100%, while understanding that physical injury is not a prerequisite for identifying sexual violence rose from 23% to 92%. Participants also demonstrated improved awareness of trauma-informed prevention and the importance of inclusive communication in digital campaigns. However, significant knowledge gaps persisted in recognizing verbal harassment as sexual violence and understanding the ethical implications of using victims’ images in digital advocacy. These findings reveal a persistent knowledge–norm gap, where technical knowledge improved but ethical awareness remained limited. The study highlights the need for multi-phase dialogic interventions that combine knowledge transfer with ethical reflection and cultural norm transformation. It also demonstrates the strategic role of women’s organizations as grassroots actors in collaborative and survivor-centered governance for sexual violence prevention.